Comparison of the Effects of Zig-Zag Run and Shuttle Run Exercises on Agility in Futsal Players - Fahri, Ana Mustafiyah; Oktaviani, Vernanda; Asyhari, Atge Oktoreza (Indonesian Journal of Medicine, 2024)
Background: Futsal players really need agility so that they can improve their performance and get maximum results as well as improve the body's physiological systems and functions. Physiotherapy plays a role in efforts to improve player achievement by optimizing physical capacity and functional abilities so that maximum achievement is achieved. Agility exercises that can be used to improve agility are obstacle runs, zig-zag runs, and shuttle runs. The purpose of this study is to find out which has a greater effect between the addition of zig-zag run and shuttle run exercises on the agility of futsal players.Subjects and method: This was an experimental study to compare the effect of zig-zag run and shuttle run on agility. 30 futsal players aged 18-23 years were divided into two groups, i.e. zig-zag run and shuttle run, randomly. The dependent variable was agility. The independent variables were zig-zag run and shuttle run. Difference of agility score before and after intervention between groups was tested using independent t-test.Results: There was no difference of agility level between zig-zag run (Mean= 10.06; SD= 0.49) and shuttle run (Mean= 10.02; SD= 0.74) groups before intervention, p= 0.315. After intervention, there was a slight difference of agility level between zig-zag run (Mean= 9.77; SD= 0.43) and shuttle run (Mean= 9.73; SD= 0.74) groups, and it was marginally significant (p= 0.052). Conclusion: After intervention, there is a slight difference of agility level between zig-zag run and shuttle run groups, and it is marginally significant.